Role-Players Affecting Audit Firm Rotation in KwaZulu-Natal: Array - Chetty, Yoshin; Deodutt, Leo Jugjith (The Journal of Accounting and Management, 2020)
Abstract: Objectives: This study aimed to provide insight into the key role-players in the rotation process from the perspective of accounting and auditing professionals. The study ultimately will provide guidance for auditors as they attempt to navigate the new mandatory audit firm rotation (MAFR) rule which is applicable to all Johannesburg Stock Exchange-listed companies from April 2023. Prior Work: The study builds on the knowledge of the interaction of auditors and firm managers. Approach: The study utilized a qualitative exploratory methodology in the form of in-depth interviews with selected industry players. Results: The findings of the study reveal practices recommended by audit practitioners in order to deal with MAFR, such as improved training and more time being allowed to onboard clients. The participants further point out actions that can be performed by specific role-players. This study is unique in KwaZulu-Natal as it surveyed auditors and audit clients. Implications: The finding will change the way auditing professionals create their strategies to deal with MAFR. It also provides basis for understanding the dynamics of interpersonal relationships in an audit. Value: The study contributes to the existing literature in that it focuses on the actual roles of the key groups and key factors in the audit firm rotation process. In addition, it has revealed the perceptions of audit clients